Understanding the commencing student mindset to better support student success: A typology of first-year students’ motivation, preparedness and perceived support - Midford, Sarah; James, Sara; Kanjere, Anastasia (Journal of University Teaching and Learning Practice, 2023)
This article presents a typology of student mindset on commencing their studies at university. Using the results of a sample of over 400 first-year humanities students enrolled in a generalist degree at a mid-tier metropolitan university, we performed a cluster analysis informed by self-reported student motivation, preparedness and perceived support. Four types were generated: the ‘Coasters,’ the ‘Reluctants,’ the ‘Passionates’ and the ‘Fight or Flights.’ The types generated exhibit a statistically significant correlation with final grade achieved. The predictive power of the generated types indicates that this form of typology is an appropriate conceptual model for understanding student success in the first-year context. As participation in higher education widens, scholarship has triggered a rethinking of the factors that determine student engagement and success across increasingly diverse cohorts. Our analysis shows that student mindset on commencing university, in conjunction with other factors including socio-economic circumstances and course preference, has significant impact on student success.